KARAKTERISTIK IKAN AIR LAUT YANG DI KONSUMSI DI KOTA DUMAI SEBAGAI RANCANGAN BUKU SAKU PADA MATERI KEANEKARAGAMAN HAYATI DI SMA KELAS X - Tini Anggraini Simamora; Imam Mahadi; Darmadi Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Fish is a food that provides relatively high protein, and contains various minerals, besides that fish can also increase the growth and development of children's intelligence to the maximum. Through this research, it is hoped that it can provide an understanding to the public about the importance of fish for public health, and introduce the benefits of eating fish to the younger generation, especially to students at school. This research was conducted for 3 months from July to September 2020. The data collected were primary data and secondary data. Primary data is data obtained through direct observation at TPI Dumai City, traditional markets, interviews with fishermen and traders (respondents). Secondary data is fishery statistical data obtained from relevant agencies, namely the Dumai City TPI and the Dumai City Fisheries and Marine Service. The results of the study on the diversity of marine fish species consumed in the city of Dumai found there were 34 families consisting of 51 fish species, In this study, the most dominating types of fish at the observation site were happy fish with 830 fish and mackerel with 766 fish, which were then developed into a pocket book design. This pocket book is used as a learning resource for students on biodiversity material related to the results of this research. The stage of making this pocket book begins with compiling and developing the material, completing the material with photos and pictures documenting the results of data collection that has been carried out.Key Words: Characteristics of Fish Species, Dumai City, Pocket Book